KEBEBASAN BERAGAMA DALAM PERSPEKTIF HADIS - Misrah Misrah (State Islamic University North Sumatra, 2010)
Abstract: Religious Freedom in the Perspective of Prophetic Traditions. Al-Qu’ran Paradigm concerning to belief have the character of personal-privat and cannot be forced the becoming one of the Islam peaching to constructing the harmonious relation and foundation between religion and fellow being. (Q.S. al-Baqarah/2: 256). This matter indicated to shall no constraint for someone in embracing a religion, including to embrace the Islam. If to embrace the just religion of others may not be forced, more than anything else punish to kill the others prohibited in Islam. War in Islam only resistance effort done to the enemy attack bother, menace safety and dissipate the Islam people through clear orders (not abysmal of boundary).Kata Kunci: keyakinan, kebebasan, perdamaian, hadis